2022
DOI: 10.1557/s43578-022-00628-9
|View full text |Cite
|
Sign up to set email alerts
|

Images of chemical structures as molecular representations for deep learning

Abstract: Implementing Artificial Intelligence for chemical applications provides a wealth of opportunity for materials discovery, healthcare and smart manufacturing. For such applications to be successful, it is necessary to translate the properties of molecules into a digital format so they can be passed to the algorithms used for smart modelling. The literature has shown a wealth of different strategies for this task, yet there remains a host of limitations. To overcome these challenges, we present two-dimensional im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Recent work assessed different molecular representations for use in chemical applications focusing specifically on tasks relevant to the field of solid form engineering. 11 This demonstrated that images of chemical structures offer the best accuracy among the methods tested. Despite this, the work is recent, and as such other chemical applications beyond those presented have not been tested using images as inputs.…”
Section: Molecular Feature Generation and Pre-processingmentioning
confidence: 94%
See 4 more Smart Citations
“…Recent work assessed different molecular representations for use in chemical applications focusing specifically on tasks relevant to the field of solid form engineering. 11 This demonstrated that images of chemical structures offer the best accuracy among the methods tested. Despite this, the work is recent, and as such other chemical applications beyond those presented have not been tested using images as inputs.…”
Section: Molecular Feature Generation and Pre-processingmentioning
confidence: 94%
“…ResNet models were chosen as a result of previous evidence of image-based deep learning models used in chemical applications and wider image recognition tasks. 11,13 These models were trained and evaluated using stratified cross-validation, from which the mean accuracy was recorded across the splits. The batch size was 256 for the CSD dataset and 8 for the in-house experimental dataset.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations